The impact of timing on outcomes of carotid artery stenting in recently symptomatic patients. (30th October 2009) - Lin, R; Mazighi, M; Yadav, J; Abou-Chebl, A
Abstract : Objectives: We sought to determine whether the timing of carotid artery stenting (CAS) affects peri-procedural outcomes in recently symptomatic patients. Background: Early carotid endarterectomy following a stroke lowers the risk of recurrent ischemic events but has been associated with an increased risk of intracerebral hemorrhage. The optimal timing of CAS following a stroke is unknown. Methods: Using a single-center prospective CAS registry, we retrospectively analyzed data on consecutive CAS procedures over an 8-year period. Patients were separated into early (≤4 weeks) and late (>4 weeks) treatment groups based on time to CAS from symptom onset. Post-procedural hypertension was treated. Thirty-day incidence of stroke, intracerebral hemorrhage, myocardial infarction and death were recorded. Results: A total of 224 patients were treated for symptomatic lesions. The mean age was 71±10 years, and 63% were men. The median time for CAS was 8 days (0.2–30 days) and 90 days (31–180 days) respectively, for the early (n=122) and late (n=102) intervention groups. There were 4 (3.45%) periprocedural strokes in the early and 5 (5.95%) in the late CAS group (p=0.5). There was one hyperperfusion syndrome in each group. The 30-day stroke, myocardial infarction or death rates were similar between the early (6.03%) and late (8.33%) CAS groups, p=0.58. A multivariate analysis showed that age >80 years rather than timing of CAS was associated with adverse events. Conclusions: CAS may be performed safely immediately following non-disabling strokes. Octogenarians may be at higher risk of complications.